A CRITICAL REVIEW ON FATIGUE ASSESSMENT APPROACH IN SHIP STRUCTURAL DETAILS - Ariesta, Rizky Chandra; Frestiqauli, Santi; Safa’at, Ahmat; Pradesar, Yusuf; Kallur, Abhishek (Journal of Marine-Earth Science and Technology, 2024)
Review of the methods used in the fatigue analysis of structures has been widely used. The resulting fatigue is primarily the result of repeated loads acting on the structure both internally and externally. Internal loads are caused by the cargo loading and unloading process, while external loads are caused by sea waves. The interaction of the two loads affects the strength of the structure. In this paper, we will discuss materials, residual stresses and environmental factors that cause fatigue in structures. The focus of analysis in this critical review is on the structural details of the ship. In determining fatigue in detailed structures, it can occur in welded joints, section cuts and shape imperfections.